CBL-B - An upcoming immune-oncology target - Fusco, Riccardo; Saedi, Zeinab; Capriello, Imma; Lubskyy, Andriy; Dömling, Alexander (Expert opinion on therapeutic patents, 2025)
INTRODUCTION: The E3 ubiquitin ligase Cbl-b is a novel target in immune-oncology, with critical roles in regulating T-cell activation and signaling pathways. By facilitating the ubiquitination and degradation of key signaling proteins, Cbl-b modulates immune responses, maintaining immune homeostasis and preventing unwarranted T-cell proliferation. The therapeutic potential of Cbl-b as a cancer immunotherapy target is underscored by its contribution to an immunosuppressive tumor microenvironment, with efforts currently underway to develop small-molecule inhibitors. AREAS COVERED: We reviewed the small molecules, and antibody-drug conjugates targeting Cbl-b from 2018 to 2024. The patents were gathered through publicly available databases and analyzed with in-house developed cheminformatic workflow, described within the manuscript. EXPERT OPINION: Targeting Cbl-b presents a promising approach in immuno-oncology, offering a novel pathway to potentiate the immune system's ability to combat cancer beyond PDL1/PD1 inhibition. The development and clinical advancement of Cbl-b inhibitors, as evidenced by the ongoing trials, mark a significant step toward harnessing this target for therapeutic benefits. Overall, the strategic inhibition of Cbl-b holds substantial promise for improving cancer immunotherapy outcomes, heralding a new era in the fight against cancer.
Keywords: Molecular Targeted Therapy; Proto-Oncogene Proteins c-cbl; Tumor Microenvironment; signální transdukce; T-Lymphocytes; nádorové mikroprostředí; protoonkogenní proteiny c-cbl; antibody drug conjugate; T-lymfocyty; adaptorové proteiny signální transdukční; Signal Transduction; Antineoplastic Agents; vyvíjení léků; CBL-B; Neoplasms; immune oncology; Drug Development; imunoterapie; zvířata; protinádorové látky; Humans; Adaptor Proteins, Signal Transducing; Patents as Topic; automated patent analysis; nádory; Immunoconjugates; Immunotherapy; cílená molekulární terapie; imunokonjugáty; small molecule; patenty jako téma; lidé; Animals